З історії українського романтичного руху: творчість М. Петренка - Барабанова, О. (Питання літературознавства, 2009)
Робиться спроба комплексного аналізу філософсько-естетичного фундаменту творчості автора з урахуванням еволюційних процесів, які спостерігались в українському романтизмі на різних етапах його розвитку. Простежуються індивідуальні особливості творчості українського романтика першої половини ХІХ ст. Михайла Петренка, визначається місце його творчості в контексті українського романтизму ХІХ ст. The article analyses the individual feature of the creative work of the Ukrainian romanticist of the first half of the 19th century, Michael Petrenko. The fiction originality of M. Petrenko`s poetry is defined, the typological and historical and comparative methods of investigation are used. It is made the attempt of the complex analysis of the philosophical and aesthetic fundamentals of the author`s creative work with the account of the evolution process that may be viewed in the Ukrainian romanticism at the different stages of its development.